(untitled) (Information systems and technologies security, 2023)
Audio file steganography can be used as an effective and efficient method to hide messages, but it is a complex process because the human auditory system is sensitive to small changes in audio data. In this article an improved approach for hiding secret text message in audio is presented, combining steganography and cryptography. The Least Significant Bits (LSB) technique, one of the most common and basic methods of steganography, is used as an algorithm for steganographic transformation. The described point of this method is to replace the least significant bits of the audio container with message bits that contain not very useful information, so filling them with additional information has little effect on the quality of perception. Such a significant disadvantage as the low level of reliability is improved by the introduction of a cryptographic layer, the feasibility of which is justified in the article. Cryptographic protection has been added in the form of one of the modern symmetric encryption algorithms – the AES algorithm in the CBC mode. Pseudo-random numbers are used to create a stable cryptokey. The cryptoalgorithm is used to protect the message, which after cryptographic conversion is hidden in the audio file using the steganographic LSB method. The main characteristics of the stegosystem are analyzed. In this paper, the application system of steganographic protection of information in audio files using a cryptographic algorithm is implemented using the environment of Microsoft Visual Studio 2019 and cryptographic libraries, the programming language is C ++. A WAV audio file was used as the digital container. NIST tests were used to assess resistance to stegoanalysis, which according to the results is better using an improved method compared to the classical LSB approach. In addition, the steganographic algorithm is evaluated by visual analysis by comparing the original audio file and the stegofile with the hidden message. The results of the analysis indicate the absence of traces of steganography. Based on the obtained results, it can be argued about the reliability and efficiency of the proposed approach, so the use of LSB-AES technique can be proposed to ensure secure data transmission.